Long-term apical bone gain after implant placement combined with internal sinus-floor elevation without graft - Rammelsberg, Peter; Pahle, Julia; Büsch, Christopher; Zenthöfer, Andreas (BMC oral health, 2020)
Background To assess changes in apical bone height/bone gain over up to 8 years after implant placement combined with simultaneous internal sinus-floor elevation (ISFE) without use of graft. Methods 217 implants were placed in combination with graft-free ISFE and successfully healed in the posterior maxilla of 138 patients. Radiographs after surgery across an evaluation time of up to 8 years were analyzed. Changes in apical and marginal bone height related to the implants were measured. Differences in bone height over the study period were evaluated by use of Wilcoxon tests. To identify possible influencing factors on apical bone gain and marginal bone loss, backward linear regression variable selections and linear mixed regression models were performed. Results At the apical aspects of the implants, significant mean vertical bone gain of 2.4 mm (mesial) and 2.6 mm (distal) was observed after 6 months (p < 0.05). Radiographic analysis yielded additional bone gain of up to approximately 3.5 mm over the study period. Small initial bone height was crossed with more pronounced apical bone gain (p < 0.05). Conclusions If implants are placed combined with graft-free ISFE, significant vertical bone gain, especially in the first year post-op, can be expected. Smaller initial bone height is associated with a higher likelihood for greater bone gain.